A politics of placelessness? The limits of democratising memory in the Centro de Documentación e Investigación of Lima's Lugar de la Memoria. (June 2021) - Willis, Daniel
The Centro de Documentación e Investigación (CDI) is an online archive which provides free access to over 20 collections on Peru's internal armed conflict (1980–2000), a conflict which was distinctly shaped by racial and social inequalities. The digital nature of the archive is presented as an opportunity for democratising access to these historical sources and for promoting commemoration as a means of cultural reconciliation. However, there is a risk that pre-existing social geographies and material concerns will mean that the CDI replicates offline exclusions. This article argues that, whilst the CDI has made these documents accessible to a broader geographical audience, usage of the digital archive is still largely mediated through social hierarchies. Through its online archive and offline engagement activities, the CDI appears to have generated a more geographically distributed network of content producers, but one which remains biased towards university-educated participants in urban areas.